1987
DOI: 10.1007/bf00541377
|View full text |Cite
|
Sign up to set email alerts
|

Degradation in vivo of articular cartilage in rheumatoid arthritis and juvenile chronic arthritis by cathepsin G and elastase from polymorphonuclear leukocytes

Abstract: Peroxidase-anti-peroxidase (PAP) staining and specific antibodies against cathepsin G and elastase from polymorphonuclear leukocytes (PMN) were applied to pannus-free and microscopically intact superficial articular cartilage. Restricted local deposits containing cathepsin G and elastase were found in three of ten patients with seropositive rheumatoid arthritis (RA), in one of three patients with seronegative RA and in one patient with juvenile chronic arthritis (JCA). Similarly, localized deposits of IgG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Moreover, TN&I-AT and TN/~2-MG molar ratios correlated negatively with serum inflammatory markers in RA patients. It appears that although the proteinase inhibitors are produced in high concentrations in the affected joints, due to some negative feedback mechanism, they are unable to prevent cartilage destruction [35][36][37]. This could be due to the binding of elastase and cathepsin G to cartilage, which localises the activity of these proteinases and protects them from the action of cq-AT, c~ -MG and other inhibitors [35,36].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, TN&I-AT and TN/~2-MG molar ratios correlated negatively with serum inflammatory markers in RA patients. It appears that although the proteinase inhibitors are produced in high concentrations in the affected joints, due to some negative feedback mechanism, they are unable to prevent cartilage destruction [35][36][37]. This could be due to the binding of elastase and cathepsin G to cartilage, which localises the activity of these proteinases and protects them from the action of cq-AT, c~ -MG and other inhibitors [35,36].…”
Section: Discussionmentioning
confidence: 97%
“…HLE has also been shown to bind avidly to cartilage [119,120] and catalytically active HLE has been localized at the cartilage-panus junction of patients with rheumatoid arthritis [121]. Moreover, cartilage-bound enzyme has been shown to be catalytically active yet substantially resistant to inhibition by both ␣ 1 -proteinase inhibitor and ␣ 2 -macroglobulin in vitro [120,122].…”
Section: Serine Proteinasesmentioning
confidence: 99%
“…Neutrophils are numerous in the inflamed joint in the early stages of rheumatoid arthritis and during acute flare-ups of the disease (3). Neutrophils have been detnonstrated in eroded areas of cartilage, particularly at the cartilage-pannus junction (4)(5)(6) and have been implicated in cartilage injury (4,5). We have shown that human neutrophils can damage human articular cartiCorrespondence: Dr I. C. Kowanko.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of this neutrophii-mediated damage is not well understood, but has been attributed largely to the lysosomal proteases, particularly elastase (5,(9)(10)(11)(12). Reactive oxygen metabolites produced during the respiratory burst may also be involved (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%